Software Athenas; An instrument for the Detection of Sport Potentialities (original) (Revista científica Olimpia, 2015)
The Software Athens it is an informatics application designed and developed to be a processing tool for the sport test results on potentials detection methodology on children of 9 and 10 years old, which is has been applied since 2013 on the Cuban province of Granma with the objective of select and provide initiation for several sport branches from different institutions. Its design includes the programming of the events in every category, percentile calculus based on tests results, related to competitors involved in every event. Also allow to classify the potentials of every contester depending on the level that reach the contester in the event.
Keywords: informatics application; potentials detection; methodology; data processing